2011
DOI: 10.1177/0894486510396705
|View full text |Cite
|
Sign up to set email alerts
|

Family Ownership and Control, the Presence of Other Large Shareholders, and Firm Performance: Further Evidence

Abstract: This article analyzes, using various econometric techniques, how family ownership, family control, and the presence of a second significant shareholder affect firm performance. The authors studied a panel of 118 nonfinancial Spanish companies (711 observations) from 2002 to 2008. Once endogeneity issues were considered, it was found that family ownership did not influence profitability. What seems to matter is family control. This study also reveals the importance of taking into account unobservable heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 65 publications
4
99
0
3
Order By: Relevance
“…This situation will become worsen if the BOC does not conduct effective surveillance. This is in line with studies by Sacristán-Navarro et al (2011) who found that family involvement in management as chief executive managers can improve the performance of the firm, but the presence of BOD members from outside the family can improve firm performance. The study is connected with the negative influence of increased control mechanisms that have families through participation in firm management.…”
Section: The Effect Of Family Involvement In Bod On Firm Performancesupporting
confidence: 76%
See 1 more Smart Citation
“…This situation will become worsen if the BOC does not conduct effective surveillance. This is in line with studies by Sacristán-Navarro et al (2011) who found that family involvement in management as chief executive managers can improve the performance of the firm, but the presence of BOD members from outside the family can improve firm performance. The study is connected with the negative influence of increased control mechanisms that have families through participation in firm management.…”
Section: The Effect Of Family Involvement In Bod On Firm Performancesupporting
confidence: 76%
“…The presence of family members in the BOC is measured by using a dummy variable, where a value of 1 is given if there are family members in BOC and otherwise, a value of 0 is given if there is no family presence in the BOC. Consistent with the previous studies, this study measures the natural logarithm of the firm size based on total assets of the firm (Bharathi, 2010;Sacristán-Navarro et al, 2011). The R&D expenses used to overcome the difficulties in getting the amount of R & D for each firm by the family firms is smaller than that used by firms without family (Villalonga & Amit, 2006).…”
Section: Va = I + Dp + D + T + M + Rsupporting
confidence: 54%
“…Family ownership is a ratio of family-owned shares to the total firm's shares (Anderson & Reeb, 2003 (Anderson & Reeb, 2003;Martinez et al, 2007). Firm age is calculated as the natural log of the number of years since the firm's inception (Anderson & Reeb, 2003;Martinez et al, 2007;Andres, 2008;Adams et al, 2009;Isakov & Weisskopf, 2009;Sacristan-Navarro et al, 2011). Firm size is measured as the natural log of the book value of total assets (Anderson & Reeb, 2003;Martinez et al, 2007;Sacristan-Navarro et al, 2011).…”
Section: Empirical Modelmentioning
confidence: 99%
“…As a result, the topic of family business takes a special place in academicians and practitioners' writings, as evidenced by the amount of research dedicated to it (e.g., Astrachan & Shanker, 2003;Rutherford, Kuratko, & Holt, 2008). On the basis of these activities, family firm performance is considered an important variable in the context of financial and management research (Sacristan-Navarro, Gomez-Anson, & Cabeza-Garcia, 2011) and commonly known as a distinct and important field of study (Walsh, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a major motivation of owners is to preserve their socioemotional wealth, and they may take less efficient or higher-risk decisions to achieve this desired result (Kalm & Gomez-Mejía, 2016). As the family's desire to avoid socioemotional losses is considerable, this objective influences the long-term performance of family firms and may be the reason why the empirical research has shown mixed results on the effects of family ownership on firm performance (Anderson & Reeb, 2003;Villalonga & Amit, 2006;Barontini & Caprio, 2006;Sacristán-Navarro, Gómez-Ansón, & Cabeza-García, 2011).…”
Section: The Relationships Between Majority and Minority Shareholdersmentioning
confidence: 99%